Photodynamic therapy with methyl aminolaevulinate 80 mg g−1 for severe facial acne vulgaris: a randomized vehicle‐controlled study4. (28th February 2016) - Pariser, D.M.; Eichenfield, L.F.; Bukhalo, M.; Waterman, G.; Jarratt, M.; ,
Summary: Background: Severe acne vulgaris has limited therapeutic options. Objectives: To evaluate photodynamic therapy (PDT) using topical methyl aminolaevulinate (MAL, 80 mg g − 1 ) as the photosensitizer in severe facial acne. Methods: A double‐blind, randomized, vehicle‐controlled multicentre trial in 153 patients (aged 12–35 years) with severe facial acne [Investigator's Global Assessment (IGA) score 4; 25–75 inflammatory lesions with ≤ 3 nodules; 20–100 noninflammatory lesions]. Treatment (four treatments 2 weeks apart) involved incubation with MAL ( n = 100) or vehicle cream ( n = 53) for 1·5 h under occlusion, then illumination (635‐nm red light, total dose 37 J cm − 2 ). IGA assessment and standardized lesion counts were performed before each treatment and 12 weeks after the first treatment. Treatment success was defined as improvement from baseline in IGA by ≥ 2 grades at 12 weeks. Safety assessments were for pain (10‐cm visual analogue scale, immediately after illumination), erythema (four‐point rating scale) and adverse events. Results: At 12 weeks, PDT using MAL 80 mg g − 1 reduced inflammatory lesions vs. vehicle PDT (mean change −15·6 vs. −7·8, P = 0·006; mean percentage change −37·3% vs. −16·2%, P = 0·003). However, noninflammatory lesions did not decrease significantly (mean change −11·8 vs. −10·7, P = 0·85; mean percentage change −28·6% vs. −24·9%, P = 0·72). Treatment success rates were greater with MAL‐PDT 80 mg g −1 (44% vs. 26%, P = 0·013). Pain was low and manageable by briefly pausing illumination. There was similar pain or erythema with successive treatments. Conclusions: PDT using topical MAL 80 mg g −1 and red light may offer promise for severe acne vulgaris. Abstract : What's already known about this topic? Severe acne substantially impacts patient quality of life. Oral isotretinoin, the mainstay of treatment, has problematic side‐effects and is teratogenic, and reimbursement may limit its use. The level of evidence is lower for systemic antibiotics. What does this study add? This trial suggests promise for photodynamic therapy using topical methyl aminolaevulinate (80 mg g −1 ) as an alternative option for severe acne. Longer duration of follow‐up and evaluation of patient satisfaction are needed. Linked Comment: Taylor. Br J Dermatol 2016;174: 712–713 . Plain language summary available online